Finanšu risku pārvaldīšana izmantojot hedžēšanu - Kabanovs, Ņikita (Latvijas Universitāte, 2011)
Bakalaura darba temats – „Finanšu risku pārvaldīšana izmantojot hedžēšanu”. Darba mērķis ir izpētīt finanšu risku hedžēšanas teorētiskus un praktiskus aspektus, uz analīzes pamata izdarīt secinājumus un izstrādāt priekšlikumus par hedžēšanas stratēģiju izmantošanu finanšu risku pārvaldīšanā uzņēmumos un komercbankās. Galvenie secinājumi: Atkarībā no riska veida un izvēlēta atvasināta finanšu instrumenta, hedžēšanas stratēģijas būtiski atšķiras, kas savukārt ietekmē riska samazināšanas efektivitāti un izmaksas saistītas ar hedžēšanu. Tomēr hedžēšana ļauj ievērojami samazināt tirgus riskus. Autors izvirzīja priekšlikumu, ka uzņēmuma vadībai jānovērtē iespējas izmantot hedžēšanu savā finanšu risku pārvaldīšanas stratēģijā, jo atsevišķos gadījumos ar hedžēšanu var gandrīz pilnīgi novērst noteiktu risku. Ka arī uzņēmumu finanšu risku pārvaldniekiem jāpārbauda visi pieejamie instrumenti kā instrumentu hedžēšanas stratēģijā un noteikta riska pārvaldīšanā. Darbs sastāv no 85 lapām teksta, 22 tabulām un 25 attēliem. Darba izstrādē izmantoti 48 informācijas avoti. Darbam ir 8 pielikumi uz 17 lapām.

Bachelor thesis topic – „Financial risk management using hedging”. The topic of the thesis was chosen because risk management is a vital process in each company regardless of the company’s industry, as well as hedging is one of the methods to manage various financial risks. The goal of the thesis is to analyze financial risk hedging theoretical and practical aspects, basing on the made analysis make conclusions and proposals for the hedging strategy usage in financial risk management in enterprises and commercial banks. Basing on the made analysis author made several conclusions and proposals to enterprises’ management for the improvements in companies’ financial status. Main conclusions: hedging strategies may differ depending on derivative used and risk hedged, therefore it influences effectiveness of the risk management and expenses connected with the hedge. Although it is possible to considerably decrease the risk exposure using hedging strategies. Basing on the conclusions made author proposed companies’ management to evaluate a possibility for hedge usage in their risk management process because hedging can considerably decrease the level of risk exposure. As well as, financial risk managers must estimate all available derivatives as an instrument in hedging of a certain risk because it is possible to increase the effectiveness of the hedge and/or decrease the costs connected with hedging by changing one hedging instrument to another. Thesis consists of 85 pages of text, 22 tables and 25 images. During the thesis working out 48 information sources were used. Thesis contains 8 appendixes on 17 pages.
Financial risk management using hedging
Keywords: Ekonomika